THE USE OF CLASSROOM BLOG IN TEACHING WRITING TO JUNIOR HIGH SCHOOL STUDENTS - Eugenia Ines Dwi Artvianti (Journal of English and Education, 2013)
This paper reports on the investigation of the implementation of classroom blog in teaching writing to the second graders in one of public schools in Bandung. The strengths and challenges faced by the students in using classroom blog as a learning tool to write are also described. A case-study design was used in the study and the data were collected through observation, interview and document analysis. Then, the data were analyzed qualitatively. The results were in line with the previous research (Song Chan, 2008; Zhang, 2009; and Galien, 2010) which stated that classroom blog helps activate interaction with readers, and create an audience and feedback for their writing. The study also found that classroom blog had its strengths and challenges. Classroom blog enabled the students to: (1) have a fun learning environment; (2) write easily; (3) get feedbacks from teacher and peers; (4) discuss more with friends and teacher outside classroom easily; (5) access more reference for students’ writing; (6) get more motivation to write; (7) have their personal space to read and write in a community; and (8) build their analytical and critical thinking skill. There were also some challenges faced by the students, as follows: (1) technical problems; (2) time management; (3) students’ inability to point out mistakes done by their peers; and (4) plagiarism. Overall, the use of classroom blog created positive effects to the students’ writing fluency. For that reason, classroom blog is recommended to be used as writing media for students.Keywords: Classroom Blog, Writing, Junior High School